Celebrating Adam Watkins' 4th Birthday at Special Spot - Watkins, Howard::::::::: (1982)
Devon Bleile-Kratzer, ?, Seth Tilley, Annie Tilley, Adam Watkins blowing out candles on cake, Sandy Jones, Art Wille, Clay Quentin ? Held at Huntington Blvd. home of Jim Kratzer and Nancy Bleile